The Ornstein–Uhlenbeck semigroup in finite dimension - Lunardi, A. (Philos Trans A Math Phys Eng Sci, 2020)
We gather the main known results concerning the non-degenerate Ornstein–Uhlenbeck semigroup in finite dimension. This article is part of the theme issue ‘Semigroup applications everywhere’.